Effectiveness of Reality Therapy Group Counseling to Increase The Self-Esteem of Students - Rosidi, Rosidi; Sutoyo, Anwar; Purwanto, Edy (Jurnal Bimbingan Konseling, 2018)
The purpose of this study was to examine the effectiveness of reality therapy group counseling to improve the self-esteem of State Islamic High School (MAN) Semarang City students. To purse such objective, this study used experimental method with Non-equivalent Pretest-Posttest Control Group Design. Meanwhile, there were sixteen students involved as the subjects of the study with the focus on their self-esteem (8 students joined experimental group and 8 other joined control group). Once their data were collected and analyzed by using independent sample t-test, it showed that reality therapy group counseling was effective to improve students' self-esteem (t(14) = 8,01, p < 0,01). For more, the discussion of the results of this study was directed to identify the implications of the application of reality therapy group counseling in improving students' self-esteem.